Use of tazarotene foam for the treatment of acne vulgaris - Gregoriou, Stamatis (Dove Medical Press, 2014)
Acne vulgaris is a common inflammatory chronic disease of the pilosebaceous unit. It often requires long-term treatment, resulting in increased demand for topical medications that are popular with patients in order to achieve long-term compliance. Tazarotene foam 0.1% is a novel formulation of tazarotene. We review efficacy and tolerability studies of the new formulation, and suggest a possible place for the product in the management of acne vulgaris.